Evaluation and Improvement of Pegasis Using Ant Colony Optimization - Verma, Sakshi; Abhilasha (International Journal of Computer Sciences and Engineering, 2015)
In the last few years many research work have been conducted by the researchers in the field of routing protocols in wireless sensor networks. Nowadays their main area of concern is based on routing protocols utilizing the concept of Swarm Intelligence. This dissertation deals with reducing the usage of energy in wireless sensor networks by ants traversing different paths. Ant colony algorithm is generally an optimization technique which is used to optimize the performance of ants by providing them easy way to find the shortest path as we can say nodes in real environment. The main attention of this research work is to understand the working of ant colony algorithm by using Stigmery operation in such a way that it increases the efficiency of the Pegasis protocol. The proposed work has been simulated based on the simulator MATLAB in which simulation will be performed and various parameters are used in regard of wireless sensor networks.